Association of GWTG-HF Risk Score with Major Adverse Cardiovascular Events in Acute Heart Failure Patients: A Retrospective Study in a Tertiary Hospital in Indonesia - Sumbayak, Novra Christy Grace; Hasan, Refli; Raynaldo, Abdul Halim; Haykal, Teuku Bob; Nasution, Ali Nafiah; Sarastri, Yuke (CoinReads Media Prima, 2025)
Introduction: Heart failure (HF) affects approximately 64 million people globally, contributing to high mortality, morbidity, reduced quality of life, and substantial healthcare burden. Acute heart failure (AHF) requires urgent intervention and carries elevated risks of mortality and major adverse cardiovascular events (MACE). The Get With The Guidelines-Heart Failure (GWTG-HF) risk score, originally developed for predicting in-hospital mortality in HF patients, has shown potential in forecasting MACE in certain populations. However, its association with MACE in Indonesian AHF patients remains underexplored. Method: This retrospective observational cohort study included 319 AHF patients admitted to Adam Malik General Hospital, Medan, Indonesia, from January 2024 to March 2025. Patient characteristics, GWTG-HF scores, and in-hospital MACE were recorded. Statistical analyses involved receiver operating characteristic (ROC) curves and multivariate regression. Results: Patients had a mean age of 55 years, with 54.5% males. Median hospital stay was 5 days (range 1–47). Predominant features included acute decompensated HF (65.8%), infection as etiology (46.7%), HFrEF (52.0%), coronary heart disease (62.4%), and smoking (50.8%). In-hospital MACE occurred in 20.4% of patients, primarily mortality (18.8%), increasing with GWTG-HF risk categories (low: 8.1%; moderate: 17.4%; high: 36.7%). Age, systolic blood pressure, heart rate, sodium, and blood urea nitrogen significantly influenced MACE (p<0.05). The GWTG-HF score demonstrated good predictive performance for MACE (AUC 0.759, p<0.001; sensitivity 63.2%; specificity 78.1%). Conclusion: The GWTG-HF score is significantly associated with in-hospital MACE in Indonesian AHF patients, supporting its utility as a risk stratification tool to guide clinical decisions and optimize management.